Percutaneous Vertebroplasty under Local Anesthesia for Osteoporotic Vertebral Compression Fractures: A Prospective Interventional Study - Dhruv Gupta; Varun Kumar Agarwal (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Majority of osteoporotic vertebral compression fractures (OVCFs) present with back pain and some of them with spinal deformity. PVP not only helps in pain relief but also the correction of spinal deformity with least postoperative morbidity. PVP through transpedicular approach is a minimally invasive procedure which can be done under local anesthesia, without muscle splitting, with short hospital stay and minimal complications compared to other techniques used. Aim: The aim of this study was to evaluate the functional outcomes following PVP in OVCFs under local anesthesia. Materials and Methods: This interventional study was conducted between November 2020 and October 2021 in the orthopedic department. This study included 40 patients with back pain with failure of conservative treatment for at least 3 weeks without nerve root compression sign with evidence of OVCFs on X-ray and Kummel sign positive who underwent PVP under local anesthesia. The Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) have been used for pre- and postoperative clinical assessment of the patients, and follow-up was done at 24 h, 1 month, and 6 months postoperatively. Results: Maximum patients were in the age group of 51–60 years, and 60% of the patients were females. Sixty-five percent of patients had lumbar vertebral fractures and 35% had dorsal vertebral fractures. The mean operative time of PVP was 34.78 min. The mean preoperative VAS and ODI scores were 7.03 and 42, respectively. The postoperative VAS and ODI scores were dramatically improved at each follow-up interval (P < 0.0001). The complications associated with the procedure were very less, in 5% of patients asymptomatic cement leakage was seen, 15% patients had pain at the needle site and in rest 80% no complication was seen. Conclusion: PVP has been shown to be a safe, effective, and minimally invasive alternative for the treatment of OVCFs. The procedure proved to be advantageous as it had shorter operative time, less blood loss, early recovery period, less postoperative work disability, lesser rate of complications, and scarring, clearly pointing toward a better acceptance of the percutaneous techniques.